Pendidikan Karakter dalam Permainan Tradisional Suku Sasak “Sepok Siat”: Literature Review - Anwar, Zul (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
Abstract: One type of traditional game owned by the Sasak tribe is the Sepok Siat game. This traditional game is a culture that needs to be preserved by being used as a means and medium for forming children's personalities, because in these games there are character education values that are good for children's development. Nowadays, children and the younger generation tend to prefer playing games that are considered modern and sophisticated such as online games, video games, gadgets, Play Station, and various other types of game applications that require money but have little benefit for physical development, character and social characteristics of children. This research aims to find the character education values contained in the traditional game Sepok Siat. This research is descriptive qualitative research with an ethnographic approach. Based on the research results, it was found that there are at least seven character education values contained in the traditional game